Bunkerhusen; Falsterbonäset - Petersson, Wille (My University, 2026)
This project explores the transformation of former military bunkers as complements to contemporary weekend houses in the area of Falsterbonäset, Sweden. It examines the architectural relationship between the structures in terms of their spatial, functional, and material qualities. The peninsula has developed from a seasonal area into one with permanent houses, while remnants of its military history still remain as objects that have lost their function. Central to the project is the question of how these massive concrete structures can be preserved and integrated into the exploitation without losing their historical and material identity. It explores the tension between the original function of a bunker and the ideal of a home with architecture that creates atmosphere in connection to history. The project is done as research through design, where the design process serves as the primary method to explore possibilities. Architectural tools are used to show spatial, material and structural outcomes. Theoretically the project is grounded on literature about atmospheres, materiality and adaptive reuse. Further studies of related reference projects have inspired the design. The result is a proposal for weekend houses in which the bunkers are transformed and complemented with new volumes designed for two adults with space for children or guests. Through controlled openings for light, raw materiality and contrasts between open and enclosed, the houses are created to unite history with a contemporary lifestyle. Findings suggest that adaptive reuse can function as a form of preservation. By introducing new use through a transformation it becomes a part of the preservation with a unique architecture rooted in its location.